Моделювання і прогнозування процесу інфляції в Грузії - Gogoladze, N. G. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The processes of Transition Economic are developing in the conditions of diverse disturbances which lead to deterioration of indicators on micro and macro levels. To improve the quality of management and forecasting of macroeconomic processes it is necessary to apply modern methods of modeling and control. In this paper, to solve the problem of modeling and forecasting inflation process is selected, which is one of the most important processes in many countries of the world. The analysis of the inflation process in Georgia, on the basis of which its positive and negative sides are defined, as well as the causes and consequences of the process is carried out. On the basis of the functional approach the stochastic autoregression model of the second order is constructed. This model has simple structure and high degree of adequacy of experimental data. By the method of parameters variation the differential equation is solved. On the basis of the solution of the differential equation which is used for short-term inflation process forecasting, the forecasting function is received. The resulting model will be used for the optimal control of inflation process.